A Review Paper on Pothole Detection Methods - Gandhi, Jetashri R; Jaliya, UK; Thakore, DG (International Journal of Computer Sciences and Engineering, 2019)
The growth of a country depends on the transportation services for traveling safely. Many distresses of asphalt pavements are responsible for the unsafe pavement surface. Potholes are the main reason for the distress of pavement. For detecting and repairing asphalt pavement having potholes, many methods are proposed in the literature for detecting potholes. There are many reasons for the distress of pavement surfaces like heavyweights of vehicles, an unspecified amount of materials, and environmental changes. In this paper, different methods are surveyed like vibration-based method, 3D Reconstruction, and vision-based method for detecting potholes. The vibration-based methods use an accelerometer, 3D laser method uses laser sensor, and vision-based method uses different image processing techniques for detecting potholes. 3D Reconstruction includes 3D laser method, Stereo Vision method, and Kinect Sensor method. The Vision-based method includes a 2D image-based method and Video-based method. In this review paper, the advantages and disadvantages of various methods are also discussed.